In the Kingdom of Solovia: The Rise of Growth Economics at MIT, 1956-1970 - Mauro Boianovsky; Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2013)
From its flow tide, fueled by the Cold War, to its ebbing with the anti-growth movement and the economic crises of the early 1970s, the "growthmen" of MIT stood at the center of the dominant field in macroeconomics. The history of MIT growth economics is traced from Solow's seminal neoclassical growth model of 1956 through the stabilization of growth theory in the first graduate textbooks.
Keywords: B2; B22; O4; O11; E12; E13; 330; growth theory; development economics; MIT; Robert Solow; endogenous growth models; technical progress